Synchronous Learning in Speaking Class: English as a Foreign Language Learners’ Voices - Tusino Tusino; Haidarrafiyan Perdanakusuma; Puspa Dewi; Wahju Tjahjo Saputro (Lingua Cultura, 2022)
The qualitative case study aimed to investigate EFL learners’ perceptions of synchronous learning in EFL speaking classes. Although numerous studies have been on synchronous learning, only a few pieces of literature focused on learners’ perceptions in English as a foreign language (EFL) settings. The research was conducted in a speaking course at a private university in Indonesia. Seven undergraduate learners majoring in English education program participated in the research which employed semi-structured interviews to gain participants’ views on their attitudes and benefits during distance education. Thematic analysis was employed to analyze learners’ perspectives and answer the research questions. The research’s findings reveal that learners are satisfied with synchronous applications. Synchronous learning improves learners’ motivation and develops confidence in class. However, EFL learners experience language learning boredom while they are joining a synchronous mode of learning. The perceived benefits of synchronous learning cover free learning resources, flexibility, accessibility, and task completion. The findings highlight that synchronous language learning can be an alternative for teaching speaking skills. English teachers need to implement a well-planned and well-executed synchronous learning strategy in teaching EFL speaking.